Intra-Euro rebalancing is inevitable but insufficient - Zsolt Darvas (Bruegel, 2012)
Greece, Portugal and Spain face a serious risk of external solvency due to their close to minus 100 percent of GDP net negative international investment positions, which are largely composed of debt. The perceived inability of these countries to rebalance their external positions is a major root of the euro crisis. Intra-euro rebalancing through declines in unit labour costs (ULC) in southern Europe, and ULC increases in northern Europe should continue, but has limits because: The share of intra-euro trade has declined. Intra-euro trade balances have already adjusted to a great extent. The intra-euro real exchange rates of Greece, Portugal and Spain have also either already adjusted or do not indicate significant appreciations since 2000. There are only two main current account surplus countries, Germany and the Netherlands. A purely intra-euro adjustment strategy would require too-significant wage increases in northern countries and wage declines in southern countries, which do not seem to be feasible. Before the crisis, the euro was significantly overvalued despite the close-to balanced current account position. The euro has depreciated recently, but more is needed to support the extra-euro trade of southern euro-area members. A weaker euro would also boost exports, growth, inflation and wage increases in Germany, thereby helping further intra-euro adjustment and the survival of the euro.
Keywords: 330; Auslandsverschuldung; Kaufkraftparität; Lohnstückkosten; Handelsbilanz; Lohnniveau; Eurozone; Griechenland; Portugal; Spanien